Analysis of Poverty in Area III Cirebon - Istiandari, Debby Nindya (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
This research is a study of the effect of population, mean years of school, life expectancy, and COVID-19 on poverty in Region III Cirebon districts/cities, which include Cirebon City, the Cirebon Regency, the Majalengka and Kuningan Regencies, and the Indramayu Regency. The type of data in this research is secondary data for the 2010-2021 time series and cross-sectional data for five regions, while the data analysis technique used is panel data regression analysis. Based on the analysis's findings, it was discovered that 1) There is no significant effect between population on poverty; 2) there is a significant influence between the average length of schooling on poverty; 3) there is a significant influence between life expectancy and poverty; 4) there is a significant influence between the COVID-19 dummy on poverty; 5) the fourth variable in the study together has a significant effect on poverty; and 6) the four independent variables in the study can explain changes in the poverty dependent variable by 85.09 percent.